1980
DOI: 10.1002/hlca.19800630617
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von optisch aktiven, natürlichen Carotinoiden und strukturell verwandten Naturprodukten. VII. Synthese von (3R)‐3‐Hydroxyretinol, (3R)‐3‐Hydroxyretinal und (3R)‐3‐Hydroxyretinsäure

Abstract: Synthesis of optically active natural carotenoids and structurally related compounds VII. Synthesis of (3R)-3-hydroxyretinol, (3R)d-hydroxyretinal and (3R)-3-hydroxyretinoic acid SummaryThe synthesis of (3R)-3-hydroxyretino1(7), (3R)-3-hydroxyretinal(9) and (3R)-3-hydroxyretinoic acid (5) according to the building principle C,, + C5 = C,, is reported utilizing the optically active C15-phosphonium salt 2 and the C,-aldehyde ester 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The action spectrum becomes broader at higher intensities and differs from that of the photoconversion of metarhodopsin to rhodopsin, which has a peak at ~580 nm. Free all-tram hydroxyretinal in organic solvents absorbs maximally in the near-ultraviolet range, at ~385 nm (Mayer and Santer, 1980). It is, therefore, apparent that all-tram 3-hydroxyretinal in the fly retina exists neither as the chromophore of the pigment nor in the free state.…”
Section: Photoisomerization In Vivo Of All-tram 3-hydroxyretinalmentioning
confidence: 99%
See 1 more Smart Citation
“…The action spectrum becomes broader at higher intensities and differs from that of the photoconversion of metarhodopsin to rhodopsin, which has a peak at ~580 nm. Free all-tram hydroxyretinal in organic solvents absorbs maximally in the near-ultraviolet range, at ~385 nm (Mayer and Santer, 1980). It is, therefore, apparent that all-tram 3-hydroxyretinal in the fly retina exists neither as the chromophore of the pigment nor in the free state.…”
Section: Photoisomerization In Vivo Of All-tram 3-hydroxyretinalmentioning
confidence: 99%
“…To summarize the main features of the photoisomerization, it is, firstly, highly sensitive and efficient: ~70% of the all-trans precursor can be photoisomerized by irradition of the fly with 410-430 nm light, at <1014 photons cm-~.s -~ for 1 h. Secondly, the formation of photoproduct, the 11-c/s isomer, is highly specific. Finally, the peak of the action spectrum of the photoisomerization shifts to a wavelength some 30-40 nm longer than the absorption maximum of the free all-trans 3-hydroxyretinal (386 nm in chloroform; Mayer and Santer, 1980). It is strongly suggested that the precursor, 3-hydroxyretinal, is bound to a specific binding protein, as is the case for the retinal-based pigment systems, such as the retinochrome in the cephalopod retina (Hara and Hara, 1972) or retinal-binding proteins in the honeybee retina (Pepe et al, 1976).…”
Section: All-trans 3-hydroxyretinal As a Precursormentioning
confidence: 99%
“…[16] The all-E retinals were isolated by purification of the mixture of isomers via column chromatography or HPLC, according to literature procedures. [3,11,17,18] The final products were characterized using 1 H and 13 C NMR spectroscopy; the analytical data proved to be identical to the data reported for the authentic compounds. [3,11,19,20] …”
Section: Resultsmentioning
confidence: 99%
“…Scheme 1. Synthesis of racemic 4-hydroxy-β-cyclocitral (9), safranal (10), and racemic 3-hydroxy-β-cyclocitral (11) The β-cyclocitral derivatives 9, 10, and 11 can easily be converted into the corresponding retinals 2, 3, and 4 by a HornerϪWadsworthϪEmmons (HWE) coupling with phosphonate 12 and subsequent Dibal-H reduction to obtain the intermediate β-ionylidene acetaldehydes. Repetition of the phosphonate coupling reaction and reduction gives the retinal derivatives 2, 3, and 4 as depicted in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation